2019
DOI: 10.1117/1.nph.6.4.041112
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative confocal optical coherence elastography for evaluating biomechanics of optic nerve head using Lamb wave model

Abstract: The mechanosensitivity of the optic nerve head (ONH) plays a pivotal role in the pathogenesis of glaucoma. Characterizing elasticity of the ONH over changing physiological pressure may provide a better understanding of how changes in intraocular pressure (IOP) lead to changes in the mechanical environment of the ONH. Optical coherence elastography (OCE) is an emerging technique that can detect tissue biomechanics noninvasively with both high temporal and spatial resolution compared with conventional ultrasonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…33 Therefore, Zhou et al developed the confocal ARF-OCE method to obtain the average elastic modulus of the ONH. 34 Although it has demonstrated that the ARF-OCE technique can obtain the average velocity of elastic waves, the wave velocity of each position cannot be achieved and thus its 2D distribution image cannot be realized. In this work, we combined the ARF-OCE system with the phase velocity algorithm to generate 2D phase velocity distribution images of the ONH at different IOPs and detection directions.…”
Section: Discussionmentioning
confidence: 99%
“…33 Therefore, Zhou et al developed the confocal ARF-OCE method to obtain the average elastic modulus of the ONH. 34 Although it has demonstrated that the ARF-OCE technique can obtain the average velocity of elastic waves, the wave velocity of each position cannot be achieved and thus its 2D distribution image cannot be realized. In this work, we combined the ARF-OCE system with the phase velocity algorithm to generate 2D phase velocity distribution images of the ONH at different IOPs and detection directions.…”
Section: Discussionmentioning
confidence: 99%
“…Further, despite ultrasonic elastography's great potential, it is limited by low spatial resolution. On the contrary, OCT, and its derivative elastography technique (optical coherence elastography [OCE]) [123,124] A critical aspect of ONH pathological remodeling in glaucoma is change in the architecture of the ONH's complex ECM and thus in the interaction between the ECM and resident neurons and glial cells. It has long been observed that the heterogeneous fibrous structure of the human LC is consistent with a heterogeneous distribution of mechanical deformation in the ONH, which in turn is associated with clinical patterns of preferential axonal damage [129].…”
Section: The Role Of the Optic Nerve Head And Optic Nerve Sheath Biom...mentioning
confidence: 99%
“…Further, despite ultrasonic elastography's great potential, it is limited by low spatial resolution. On the contrary, OCT, and its derivative elastography technique (optical coherence elastography [OCE]) [123,124], has superior spatial resolution, and in combination with biomechanical modeling, is a potent alternative for investigating ONH biomechanical properties in vivo [61 â–Șâ–Ș ,125 â–Ș ,126]. Interestingly, OCT-driven morphologic reconstructions of the ONH can be used to generate patient-specific computer models to study ONH biomechanics [127] and hemodynamics [128], which may eventually be used as new tools for assessing progression of ONH pathological remodeling in glaucoma.…”
Section: The Role Of the Optic Nerve Head And Optic Nerve Sheath Biom...mentioning
confidence: 99%
“…143 OCE studies have also shown that increased optic nerve head Young's modulus and posterior scleral stiffness are correlated with increasing IOP, which suggests that OCE can also be used to monitor progression of glaucoma. 144,145 Clinical utility and challenges. Both OCE and PhD-OCT technologies are in the early stages of clinical translation, and current research is focused on improving imaging speed and phase stability.…”
Section: Optical Coherence Tomographic Angiographymentioning
confidence: 99%